Transmission of US and EU Economic Policy Uncertainty Shock to Asian Economies in Bad and Good Times - Mehmet Balcilar; Zeynel Abidin Ozdemir; Huseyin Ozdemir; Mark E. Wohar (Institute of Labor Economics (IZA), 2020)
This study empirically examines the fragility of five major Asian economies (China, Hong Kong, India, Japan, and South Korea) to economic policy uncertainty (EPU) of US and EU, and oil prices in different state of the economies. To investigate these dynamics, we use the relative tail dependence by means of the spillover index of Diebold and Yilmaz (2009, 2012) obtained from Quantile Vector Autoregressive (QVAR) model, a robust and semiparametric model, which does not require specification of the full distribution of error terms. The distinguishing feature of our approach from the previous studies is the determination of sign and intensity of asymmetric spillover dynamics from external shocks to Asian economies and variables covering a wide range of macroeconomic aspects. Our results indicate that the spillover indices from EPU and oil price shocks to Asian economies significantly vary across quantiles. The results from sub-sample analysis show that the US EPU has an asymmetric effect on macro variables of China, Hong Kong, and South Korea during the quantitative easing period (QE) and the reverse QE (RQE) periods while the EU EPU makes Asian markets vulnerable during the Eurozone debt crisis. The large-scale asset purchases (LSAPs) of ECB and BoJ seem to reduce Asian market fragilities after 2015. Last but not least, we get partial evidence to support an asymmetric effect of the crude oil shocks on some Asian markets.
Keywords: C32; E44; F42; G01; 330; quantile VAR; oil price change; economic policy uncertainty; relative-tail-dependence